Elevating athletic performance : Maximizing strength and power in long jumpers through combined low-intensity blood flow restriction and high-intensity resistance training - Sarfabadi, Pehzaan; Rizvi, Moattar Raza; Sharma, Ankita; Sami, Waqas; Sajid, Mirza Rizwan; Arora, Sumit; Anand, Akshay; Mohd Rashid, Ab Hamid (Elsevier Ltd, 2023)
This study aimed to evaluate the effects of low-intensity blood flow restriction (BFR) training and high-intensity resistance training (HI-RT) on the leaping performance of long-jumpers. Materials and methods: Long jump players were divided into two groups; one group (group A) receiving HI-RT (n = 8) and the other group (group B) receiving combined low-intensity BFR training plus HI-RT (n = 8). Muscle power and knee muscle strength was assessed at baseline, 3 weeks and 6 weeks of intervention. Results: 1-RM was found to be significantly different between Group A and Group B at 3 and 6 weeks. Further, IKDQR, IKDHR and IKDQL was significantly improved in group B as compared to group A both at 3 and 6 weeks. There was significant time effect, group effect and time-group interaction in the strength of quadriceps and hamstring of both left and right leg measured through isokinetic device. Post-hoc analysis for 1-RM in group B showed a significant improvement at baseline and 6 weeks and the broad jump was significant at baseline and 3 weeks and at baseline and 6 weeks. Conclusion: The combined effects of low-intensity BFR training and HI-RT is effective in improving the muscle strength and power of lower limbs in long jumpers.